Nurses' experiences of ethical responsibilities of care during the COVID-19 pandemic. (June 2022) - Peter, Elizabeth; Mohammed, Shan; Killackey, Tieghan; MacIver, Jane; Variath, Caroline
Background: The COVID-19 pandemic has forced rapid and widespread change to standards of patient care and nursing practice, inevitably leading to unprecedented shifts in the moral conditions of nursing work. Less is known about how these challenges have affected nurses' capacity to meet their ethical responsibilities and what has helped to sustain their efforts to continue to care. Research objectives: 1) To explore nurses' experiences of striving to fulfill their ethical responsibilities of care during the COVID-19 pandemic and 2) to explore what has fostered nurses' capacity to fulfill these responsibilities. Research Design: A generic qualitative approach was used incorporating concepts coming from fundamental features of care. Participants: Twenty-four Canadian Registered Nurses from a variety of practice settings were interviewed. Ethical Considerations: After receiving ethics approval, signed informed consent was obtained before participants were interviewed. Findings: Four themes were identified. 1) Challenges providing good care in response to sudden changes in practice. 2) Tensions in juggling the responsibility to prevent COVID-19 infections with other competing moral responsibilities. 3) Supports to foster nurses' capacity to meet their caring responsibilities. 4) The preservation of nurses' moral identity through expressions of gratitude and health improvement. Discussion: Infection control measures and priorities set in response to the pandemic made at distant population and organizational levels impacted nurses who continued to try to meet the ideals of care in close proximity to patients and their families. Despite the challenges that nurses encountered, the care they received themselves enabled them to continue to care for others. Nurses benefited most from the moral communities they had with their colleagues and occasionally nurse leaders, especially when they were supported in a face-to-face manner. Conclusion: Moral community can only be sustained if nurses are afforded the working conditions that make it possible for them to support each other.